1994
DOI: 10.1007/bf00593685
|View full text |Cite
|
Sign up to set email alerts
|

3D-FT MRI of the facial nerve

Abstract: Contrast-enhanced 3D-FT MRI of the intrapetrous facial nerve was obtained in 38 patients with facial nerve disease, using a 1.0 T magnet and fast gradient-echo acquisition sequences. Contiguous millimetric sections were obtained, which could be reformatted in any desired plane. Acutely ill patients, were examined within the first 2 months, included: 24 with Bell's palsy and 6 with other acute disorders (Herpes zoster, trauma, neuroma, meningeal metastasis, middle ear granuloma). Six patients investigated more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…Interestingly, extensive tumour growth was described in this case, involving the jugular foramen as well. Two other publications, mentioning a neurofibroma in the mastoid part of the facial canal, refer to the same patient and have not been histologically verified [13,14]. The diagnosis was based on the coincidence of a facial canal tumour and the presence of NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, extensive tumour growth was described in this case, involving the jugular foramen as well. Two other publications, mentioning a neurofibroma in the mastoid part of the facial canal, refer to the same patient and have not been histologically verified [13,14]. The diagnosis was based on the coincidence of a facial canal tumour and the presence of NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Girard et al [1] reported that cases showing facial nerve enhancement on MRI may recover later than those without enhancement, and Yetiser et al [2] also showed a positive correlation between enhancement of facial nerve and the recovery time in patients with facial paralysis. However, many other reports have denied any relationship between the clinical prognosis and the extent, duration, pattern, and degree of facial nerve enhancement on MRI [3Á5, 12,15,17].…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, there are still controversies regarding the enhancement pattern of the facial nerve on MRI and its correlation with anatomical characteristics, disease severity, electrophysiologic tests, and prognosis. Some authors reported that the presence of facial nerve enhancement on MRI is associated with delayed clinical recovery [1,2], while many others demonstrated the poor prognostic value of MRI in predicting disease severity or the recovery process [3Á5]. The controversial results of different studies may be due to the heterogeneity of subjects with different prognoses included in the study, various timings at which MRI was performed after the onset of facial palsy, or the different techniques and parameters of MRI applied.…”
Section: Introductionmentioning
confidence: 96%
“…Weist ein Patient mit Trigeminusneuralgie auf der betroffenen Seite einen um 20 % dünneren Nerv im Vergleich zur gesunden Gegenseite auf, so ist dieser Befund auch mit bloßem Auge zweifelsfrei zu erkennen. Dies setzt jedoch voraus, dass bei diesem Krankheitsbild hochauflösende Sequenzen verwendet werden, mit denen solch dün-ne Strukturen wie Hirnnerven differenziert beurteilt werden können [11,12]. Ebenso wie beim asymmetrischen Enhancement gesunder Nerven nach i. v. Kontrastmittelgabe [13] spielen auch bei der Einschätzung von Volumina bei Nerven dieser Größen-ordnung Partialvolumeneffekte mit zunehmender Schichtdicke eine Rolle [14].…”
Section: Diskussionunclassified